Values and value changes of former Filipino student activists - Montiel, Cristina (1984)
This research attempted to find out the values of Filipino student activists in the pre-Martial Law days. Their value changes in early adulthood were also examined. 36 ex-activists participated in the study through mailed questionnaires that asked them about their demographic profile, some personal psychological situations, and value rankings. Five respondents in various life tracks agreed to have their biographies narrated in the form of case studies. The research examined value clusters among Rokeach's list of values through factor analysis. Multiple regression equations tested for main and interaction relationships among variables. As adolescents, the activists put primary importance on the values of freedom, equality, a sense of accomplishment, and being courageous. Results support the role of theory model of adult political socialization: changes in role expectations brought about by marriage, work and Martial Law resulted in Psychopolitical alterations. Caution, however should be taken in generalizing the findings. Results were based on an extremely small sample size that was biased in the sense of being composed only of non-underground respondents.
Includes bibliographical references (pages 71-72).